Low-intensity electrical stimulation enhances phthalate ester biodegradation by activated sludge through real-time multi-scale regulation - Huabo Gong; Zhuo-Ning Xian; Jinwen Hu; Jinming Luo; Yawei Wang; Xiaowei Liu; Nanwen Zhu (Water Research, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

A functional lactic acid bacteria strain that naturally produces hydroxytyrosol and its impact on the antioxidant activity and post-acidification of fermented milk - Panpan Han; Yangliu Liu; Min Zhang; Yinglin Chen; Simiao Zhai; Zhixin Wang; Yawei Ning; Yingmin Jia (Food Bioscience, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Functional Lactiplantibacillus plantarum MT213 screened from traditional sourdough and its promising in-situ preservation in steamed bread - Danya Tong; Yajuan Zhang; Tianyi Zhang; Zhixin Wang; Shijie Wang; Xueming Xu; Yawei Ning (International Journal of Food Microbiology, 2026)

Parental HFPO-TA exposure induces intergenerational reproductive toxicity and DNA methylation alterations in zebrafish - Shasha Dong; Xiaohui Zhao; Xuan Ren; Jing Zhang; Zhibo Liu; Dan Yang; Ning Ji; Yawei Shi; Ya Sun; Guanghui Ding (ENGINEERING Environment, 2026)

Untargeted metabolomics-based investigation of amino acid effects on antimicrobial peptides production in Paenibacillus ehimensis HD 8-3 fermentation - Chengling Feng; Jiapei Zhang; Yunfei Si; Zhen Zhao; Yawei Ning; Zhixin Wang (Food Bioscience, 2026)

An ensemble method for integrating rainfall forecast products based on average mutual information decomposition - Wei Ding; Minglei Ren; Yawei Ning; Xuan Li; Jinnan Zhang; Huicheng Zhou (Environmental Modelling & Software, 2026)

Critical nanoparticle formation in iron combustion: single particle experiments with in-situ multi-parameter diagnostics aided by multi-scale simulations - Tao Li; Bich-Diep Nguyen; Yawei Gao; Leon Elsässer; Daoguan Ning; Arne Scholtissek; Adri C.T. van Duin; Christian Hasse; Benjamin Böhm (Fuel, 2026)

Graphene/epoxy coating with radiation heat dissipation properties for spacecraft thermal management - Ning Li; Yibo Zhang; Yawei Xu; Jing Li (Chemical Engineering Journal, 2025)

Mechanism and application of phenyllactic acid on the control of yogurt post-acidification caused by Lactobacillus bulgaricus - Hongxin Zhou; Xuanxuan Pang; Panpan Han; Zhixin Wang; Shijie Wang; Yingmin Jia; Yawei Ning (Food Research International, 2025)

Mechanisms of antifungal activity of ehimensin F6 produced by Paenibacillus ehimensis HD against Penicillium expansum - Yuqing Huang; Dandan Liu; Yahui Liu; Ziwei Jia; Tengteng Zhao; Zhen Zhao; Yawei Ning; Xiaohui Liang; Zhixin Wang (International Journal of Food Microbiology, 2025)

Sucrose laurate and nisin synergistically inhibit Bacillus subtilis by multiple antibacterial targets and play promising application potential in bread preservation - Danya Tong; Panpan Han; Mingrui Li; Zhixin Wang; Zhen Zhao; Yingmin Jia; Yawei Ning (Food Chemistry, 2025)

Mechanism investigation into static magnetic field effects on enhancing surfactin productivity by Bacillus subtilis - Yamei Jin; Sirui Chen; Qiyan Zhao; Na Yang; Yawei Ning; Xueming Xu (Food Bioscience, 2025)

Nonlinear dynamic analysis of a 3D land-fixed oscillating water column wave energy converter - Dezhi Ning; Yawei Sun; Rongquan Wang; Peiwen Cong (Ocean Engineering, 2025)

Experimental investigation on seismic performance of austenitic stainless steel full-scale frames: Component response - Keyang Ning; Lu Yang; Ke Jiang; Yawei Han (Engineering Structures, 2025)

Recent advances in groundwater pollution research using machine learning from 2000 to 2023: A bibliometric analysis - Xuan Li; Guohua Liang; Bin He; Yawei Ning; Yuesuo Yang; Lei Wang; Guoli Wang (Environmental Research, 2025)

Inactivation mechanism of phenyllactic acid against Bacillus cereus spores and its application in milk beverage - Dongchun Zhang; Danya Tong; Zhixin Wang; Shijie Wang; Yingmin Jia; Yawei Ning (Food Chemistry, 2024)

Antifungal mechanism of Lactiplantibacillus plantarum P10 against Aspergillus niger and its in-situ biopreservative application in Chinese steamed bread - Mengge Ma; Ao Li; Jin Feng; Zhixin Wang; Yingmin Jia; Xinying Ma; Yawei Ning (Food Chemistry, 2024)

Alternating wet and dry irrigation cycles enhance the nitrogen “cache” function of duckweed in a rice-duckweed system - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Ning Gao; Zeeshan Ahmed; Yihao Peng; Hao Liang; Qianjing Jiang; Yong He (Agriculture, Ecosystems & Environment, 2024)

Experimental investigation on a novel and hyper-efficient oscillating water column wave energy converter coupled with a parabolic breakwater - Robert Mayon; Dezhi Ning; Yawei Sun; Zhenyu Ding; Rongquan Wang; Yu Zhou (Coastal Engineering, 2023)

Flood Risk Quantification, Transmission, and Propagation Analysis for Flood Water Utilization of Parallel Reservoirs - Wei Ding; Chi Zhang; Jie Lin; Xi Zhao; Yawei Ning; Huicheng Zhou (Journal of Hydrology, 2023)

Numerical Investigation on Higher-Order Harmonic Waves Induced by a Submerged Inclined Plate - Zhimin Zhou; Yawei Sun; Lifen Chen; Dezhi Ning; Sulisz Wojciech (Journal of Marine Science and Engineering, 2022)
In this paper, a two-dimensional time-domain numerical flume has been established to model and investigate nonlinear interactions between nonlinear surface waves and a submerged inclined thin plate. The model solves the Laplace equation and the fully nonlinear free surface boundary conditions within the framework of potential flow theory based on the high-order boundary element method. The mixed Euler–Lagrangian method is applied to update the water surface at each time step, and the fourth-order Runge–Kutta method for time stepping. A so-called four-point method was employed to separate the second-order harmonic free and bounded wave that has the same wave frequency but different wave celerity in front of and behind the submerged plate. It is found that the amplitude of the second-order harmonic free wave increases with the inclination angle of the submerged plate, and the level/amount of the increase is larger for a larger wave steepness. In addition, the amplitudes of both the second-order reflected and transmitted waves are found to increase with the wave steepness, and their empirical relationships are derived for potential use in practical engineering.

An Analytical Risk Analysis Method for Reservoir Flood Control Operation Considering Forecast Information - Yawei Ning; Wei Ding; Guohua Liang; Bin He; Huicheng Zhou (Water Resources Management, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Uncertainty analysis of SPI calculation and drought assessment based on the application of Bootstrap - Yi‐Ming Hu; Zhong‐Min Liang; Yong‐Wei Liu; Jun Wang; Lei Yao; Yawei Ning (International Journal of Climatology, 2015)
The Standardized Precipitation Index ( SPI ) has been widely used to monitor the drought status. In the estimation of SPI , an appropriate probability distribution function ( APDF ) is required to fit precipitation series with different timescales, such as 3‐month, 9‐month and so on. Then the standard normal distribution function is used to transform the cumulative probability derived from APDF to calculate the SPI value. Obviously, the estimation accuracy of SPI particularly depends on the sample that influences the selection of PDF and parameter estimation. However, the size of the observed sample is usually small, and it cannot perfectly present the statistical property of the population, which usually causes the uncertainty on calculation of SPI and in turn results in the uncertainty of drought assessment. Due to the existence of gap between the estimated SPI and the true SPI , when one obtains the estimation of SPI , it is necessary to know the reliability or uncertainty of the estimated SPI . In this article, a new method based on the Bootstrap method was put forward to analyse the impact of sampling uncertainty on the estimation of SPI and drought assessment. Through repeating samples from the original sample, a large number of Bootstrap samples are constructed, and based on each Bootstrap sample, the corresponding estimation of SPI for the given event can be obtained. Therefore, the sampling distribution of SPI for the given event can also be derived, on which both the point estimation and interval estimation of SPI for the given precipitation event can be provided, and the overall assessment of a drought event could be achieved. The case study shows that, compared with the original SPI calculation method, the proposed method not only provides equivalent assessment results, but also has the capability to assess the impact of sampling uncertainty on the uncertainty of SPI calculation and drought assessment.